Social partner characteristics as facilitatores of the wine co-creation experiences - Cunha, N.; Loureiro, S. M. C.; Sarmento, E. M. (Congresso Internacional de Turismo Activo, Desporto, Natureza e Sustentabilidade, CITADNS’2018, 2018)
This study explores a dyadic perspective of wine producers and distributors using conducting and analysing 44 in-depth interviews among members of top managers of wine producers and wine distributors. They represented 22 companies and 11 exchange relationships. Data gathered by the interviews were processed through the application of specialized software (WEBQDA) to develop the content analysis based on the Grounded Theory. Findings identify Personal Social Capabilities and Organizational Social Capabilities as new constructs of Partner Characteristics, employed to describe the Relationship Quality (RQ) between two important players of the market. The main findings highlight Personal and Organizational Social Characteristics as core elements to develop an interactive relationship quality among stakeholders.